Development through Movement – Psychopedagogical Analysis and Psychomotor Approaches - Zoglowek, Herbert; Aleksandrovich, Maria (Revija za elementarno izobraževanje, 2016)
This paper discusses psychomotor development in early childhood and consists of three parts. The first part is a brief historical overview of the theoretical description and analysis of movement. The second part gives an overview of the variety of movement therapies and activity methods, which are effective in kindergarten work. The third part of the paper is an attempt to analyse and to reflect on the authors’ own practical experiences of psychomotor work in kindergartens in Poland and Norway.
Keywords: early childhood; motor development; movement analysis; psychomotor activity; zone of proximal development